Реабілітація як самостійний процесуально-правовий інститут - Суховіліна, А. О.; Sukhovilina, A. O. (Право і безпека. - 2011. - № 4 (41). - С. 127-131, 2011)
Проведено науковий аналіз поняття реабілітації, надано визначення інституту реабілітації, визначено ознаки та структурні елементи інституту реабілітації.

The scientific analysis of the concept of rehabilitation is made, the definition of the institute of rehabilitation is given, the functions and structural elements of the institute of rehabilitation are defined.

Проведен научный анализ понятия реабилитации, дано определение института реабилитации, определены функции и структурные элементы института реабилитации.
Rehabilitation as an independent procedural and legal institute
Реабилитация как самостоятельный процессуально-правовой институт
Keywords: кримінальне судочинство; criminal justice; уголовное судопроизводство; реабілітація; rehabilitation; реабилитация; правові інститути; legal institutions; правовые институты